Respostas

2013-12-13T14:52:42-02:00
| 1   0   1 | 1   0 | 
| 2   4   3 | 2   4 | 
| x   y   5 | x   y | 

(1 * 4 * 5) + (0 * 3 * x) + (1 * 2 * y) - [ (1 * 4 * x) + (1* 3 * y) + (0 * 2 * 5)] = 6
20 + 0 + 2y - (4x + 3y + 0) = 6
20 + 2y - 4x - 3y = 6
-4x - y = -14  <--- primeira equação

| 3   1   x | 3   1 | 
| 2   y   1 | 2   y | 
| 0   3   5 | 0   3 | 

(3 * y * 5) + (1 * 1 * 0) + (x * 2 * 3) - [ (x * y * 0) + (3* 1 * 3) + (1 * 2 * 5)] = 29
15y + 0 + 6x - (0 + 9 + 10) = 29
15y + 6x - 19 = 29
15y + 6x = 48 <--- segunda equação

Realizando o sistema das equações:

 \left \{ {{-4x - y=-14} \atop {6x + 15y=48}} \right.

y = 14 - 4x

15 (14 - 4x) + 6x = 48
210 - 60x + 6x = 48
-54x = -162 . (-1)

x =  \frac{162}{54}
x = 3

Desta forma, y = 14 - 4x
y = 14 - 4 (3)
y = 14 - 12
y = 2

1 5 1